A Forensic Study of Mycosis and its Relation ‎with Amphetamine Addiction Tests - Suhailah M. Wahhoodee (Journal of Global Pharma Technology, 2018)
The abuse of amphetamines is of national concern from a public health perspective. This issuing a nowadays important subject, because the problem of amphetamine drugs has recently been raised toa very dangerous level. Amphetamines are generally prescribed as a potent central nervous system (CNS) stimulant that is used in the treatment of attention deficit hyperactivity disorder (ADHD), narcolepsy, and obesity. The present study aimed to test the ability of Fungi to bio-convert methamphetamine that may change the metabolite pattern and / or concentration of the drug. Total of 53 blood samples were collected (10 samples from drug addict prisoners at Al-Samawa prison, 30 samples from healthy (non-symptomatic), 13 sample phlegm of respiratory system patients). Samples were cultured on Blood agar then purified on Sabouraud dextrose agar. Thereafter, each isolate was cultured in 5ml Sabouraud dextrose broth containing 6mg/ml methamphetamine drug and incubated at 37ºC. Samples were tested periodically, by thin layer chromatography (TLC) using methanol and ammonia (100:1.5) as a mobile phase. The separated spots were visualized by spraying with iodoplatinate or Marquis Reagent the results revealed that 11 sample was able to convert the drug after 14 days of incubation. The TLC method found more advantageous in detecting drug bio-conversion. Add to that, it is inexpensive, fast and easy to manipulate in forensic labs.Keywords: Methamphetamine, Fungi, TLC.